Phthalate esters in the environment: A critical review of their occurrence, biodegradation, and removal during wastewater treatment processes - Gao, Da-Wen; Wen, Zhi-Dan (The Science of the total environment, 2016)
Phthalate esters are one of the most frequently detected persistent organic pollutants in the environment. A better understanding of their occurrence and degradation in the environment and during wastewater treatment processes will facilitate the development of strategies to reduce these pollutants and to bioremediate contaminated freshwater and soil. Phthalate esters occur at measurable levels in different environments worldwide. For example, the concentrations of dimethyl phthalate (DMP) in atmospheric particulate matter, fresh water and sediments, soil, and landfills are N.D.–10.4ng/m3, N.D.–31.7μg/L, N.D.–316μg/kg dry weight, and N.D.–200μg/kg dry weight, N.D.–43.27μg/L, respectively. Bis(2-ethylhexyl) phthalate (DEHP) and di-n-butyl phthalate (DBP) are primary phthalate ester pollutants. Urbanization has increased the discharge of phthalate esters to atmospheric and aquatic environments, and the use of agricultural plastics has exacerbated soil contamination by phthalate esters in rural areas. Aerobic biodegradation is the primary manner of phthalate ester mineralization in the environment, and this process has been widely studied. Phthalate esters can be removed during wastewater treatment processes. The combination of different wastewater treatment technologies showed greater efficiency in the removal of phthalate esters than individual treatment steps, such as the combination of anaerobic wastewater treatment with a membrane bioreactor would increase the efficiency of phthalate ester removal from 65%–71% to 95%–97%. This review provides a useful framework to identify future research objectives to achieve the mineralization and elimination of phthalate esters in the environment. [Display omitted] •Occurrence of phthalate esters was summarized in the different environments.•Urbanization exacerbated the discharge of phthalate esters to atmosphere and water.•Aerobic biodegradation is the primary mineralization process of phthalate ester.•Phthalate esters could be removed by biodegradation and absorption in WWTPs.